The executive council of the Malayan Federation (1948-1955) - Mohd Azhar, Mohd Azib (2014)
The purpose of this paper is to analyse the legacies of the British Malaya in the formation of the first cabinet in 1955 to 1959, as well as the extent of changes introduced by the first local leaders. The goal is to shed light on the influence of the British colonialisation on the transition of Malaya towards self-government, and whether there has been an effective transfer of power in the British policy of de-colonialisation of South East Asia.The paper studies this by examining the historical development of the first cabinet after independence until its dissolution in 1959, as well as the similarities and differences to the previous status-quo before independence.Upon examination of these events, it became clear that there were evidence of continuity from the colonial democracy structure, most notably the system of constitutional monarchy that was adopted in the post-independent Malaya. However, there were also distinguishing elements that were introduced to suit the local circumstances, as the leaders’ response to allegations of neo-colonialism.These findings are important in understanding the importance of foundation and function of the cabinet system in Malaysia. It is also envisaged that this paper will close the gap in the existing body of study within the context of Malaysian history.